Lipoma do cerebelo: relato de caso - Nai, Gisele A. [UNESP]; Montenegro, Mario R. [UNESP] (Academia Brasileira de Neurologia (ABNEURO), 1997)
Lipomas intracranianos são raros, geralmente sendo achado de autópsia. Situam-se na linha média, mais frequentemente de localização central. Podem ocorrer desde a infância até a vida adulta. Muitos dos lipomas, na verdade são associados a lesões hamartomatosas ou, mesmo, a neoplasias como os meduloblastomas do cerebelo. Relatamos e discutimos um caso de lipoma de cerebelo, achado de autópsia de um recém-nascido prematuro.

Intracranial lipomas are rare. Usually they are incidental findings at autopsy. They occur in all the age groups and are often associated with hamartomatous lesions or neoplasms as cerebellum medulloblastomas. More frequently they are central and located at the midline. We report and discuss a case of lipoma of the cerebellum, an incidental finding at autopsy of a premature newborn.
Lipoma of the cerebellum: case report
Keywords: lipoma; tumor cerebelar; malformação; lipoma; cerebellar tumor; malformation